Determinasi Keputusan Pembelian Melalui Brand Image Analisis: Product Quality dan Lifestyle Pada Konsumen Sepatu Merk Adidas di Foot Locker DP Mall Kota Semarang - Sulistiani Sulistiani; Amron Amron; Roymon Panjaitan; Pradana Jati Kusuma (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Companies are required to continue to innovate in creating new products that have high competitiveness, one of which is shoes. The purpose of this study is to determine how product quality and lifestyle influence purchasing decisions through brand image in Adidas Shoe consumers at Foot Locker Dp Mall, Semarang City. Data were collected using a questionnaire (Google Form) with 140 respondents. This study uses Smart-PLS analysis. The results of this study indicate that product quality and lifestyle have a positive and significant effect on brand image. Product quality and lifestyle have a positive and significant effect on purchasing decisions. Then, brand image has a significant effect as a mediator between product quality and lifestyle on purchasing decisions. Management needs to optimize the synergy between product quality excellence and brand image strengthening that is relevant to the dynamics of today's consumer lifestyles..